Basal cell hyperplasia and basal cell carcinoma of the prostate: a comprehensive review and discussion of a case with c-erbB-2 expression. Issue 3 (25th February 2005) - Montironi, R; Mazzucchelli, R; Stramazzotti, D; Scarpelli, M; López Beltran, A; Bostwick, D G
Abstract : Prostatic basal cell proliferations range from ordinary basal cell hyperplasia (BCH) to florid basal cell hyperplasia to basal cell carcinoma. The distinction between these forms of BCH, including the variant with prominent nucleoli (formerly called atypical BCH), and basal cell carcinoma depends on morphological and immunohistochemical criteria and, in particular, on the degree of cell proliferation. In florid BCH, the proliferation index is intermediate between ordinary BCH and basal cell carcinoma. Immunohistochemistry is also useful for identifying the cell composition of the basal cell proliferations, including the basal cell nature of the cells, their myoepithelial differentiation, and c-erbB-2 oncoprotein expression. Based on the information derived from the literature and on the appearance and follow up of the case presented here, florid BCH might represent a lesion with an intermediate position between ordinary BCH and basal cell carcinoma. However, criteria useful for the identification of those cases with a true precursor nature are not available. In general, basal cell carcinoma is seen as a low grade carcinoma. The immunohistochemical expression of the c-erbB-2 oncoprotein, similar to that seen in breast cancer, might have therapeutic importance.